2004
DOI: 10.1002/prot.20293
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mutations in tyrosine hydroxylase associated with progressive dystonia on the activity and stability of the protein

Abstract: Tyrosine hydroxylase (TyrH) catalyzes the conversion of tyrosine to dihydroxyphenylalanine (DOPA), the rate-limiting step in the biosynthesis of dopamine. Four mutations in the TyrH gene have recently been described in cases of autosomal recessive DOPA-responsive dystonia (Swaans et al., Ann Hum Genet 2000;64:25-31). All four are predicted to result in changes in single amino acid residues in the catalytic domain of the protein: T245P, T283M, R306H, and T463M. To determine the effects of these mutations on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 30 publications
2
43
1
Order By: Relevance
“…THD-associated mutations correlate with loss-of-function-misfolding and instability of TH [14][15][16], and the mutants are rapidly degraded by intracellular proteases, leading to decreased TH and dopamine levels in THD patients. Increasing evidence points to pharmacological chaperones as a promising therapeutic strategy for loss-offunction misfolding diseases [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…THD-associated mutations correlate with loss-of-function-misfolding and instability of TH [14][15][16], and the mutants are rapidly degraded by intracellular proteases, leading to decreased TH and dopamine levels in THD patients. Increasing evidence points to pharmacological chaperones as a promising therapeutic strategy for loss-offunction misfolding diseases [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of silent SNPs should also be analyzed [4]. Since the locations of all SNPs identified in this study were different from those of SNPs in human TH and DBH genes, possible structural and functional changes derived from these SNPs should be examined as have been reported for human genes [7,33,34]. With regards to the breed differences of these SNPs, C97T on the TH gene and A1819G on the DBH gene are only found in Shibas.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, several deletion and missense mutations, more than 20 noncoding SNPs, and various synonymous coding and nonsynonymous coding SNPs, a splice junction mutation, and at least three promoter mutations have been reported in the TH gene (Supplementary Table S1). Expression analysis and biochemical characterization of the missense mutant enzymes have revealed that they have either normal or decreased enzymatic activity (V max ) in vitro, but all seem to have decreased thermal stability in vitro [Knappskog et al, 1995;Ludecke et al, 1996;Royo et al, 2005], similar to what has been found for the ''mild'' variants of PAH associated with PKU (www.pahdb.mcgill.ca).…”
Section: Mutations Within Theth Genementioning
confidence: 61%